The role of renin-angiotensin system and angiotensin-converting enzyme 2 (ACE2) in the development and course of viral infection COVID-19 in patients with diabetes mellitus - O. K. Vikulova; Zamira Zuraeva; L. V. Nikankina; M. V. Shestakova (Сахарный диабет)
The role of renin-angiotensin system (RAS) in general and angiotensin-converting enzyme 2 (ACE2) in particular in the  pathogenesis and course of viral infection caused by SARS-CoV-2 (COVID-19) is of particular interest. This is due not only to the fact that ACE2 is a receptor for the virus the target cells. RAS hyperactivation in patients with arterial hypertension, cardiovascular disease and diabetes mellitus, is considered one of the most important factors for a more severe infection in persons with concomitant pathology. In addition, the effects of PAS blockage with angiotensin converting enzyme inhibitors (ACE inhibitors) and angiotensin II receptor blockers (ARBs) remains one of the most discussed topics in the literature on COVID-19. This review presents the data on the interaction between the virus and the main components of RAS and the factors influencing their expression level, the impact of ACE inhibitors and ARBs therapy on the disease outcome, and presents the perspectives of the treatment with recombinant ACE 2.